Reproductive biology of male common dolphins (Delphinus delphis) in New Zealand waters - Emily I. Palmer; Emma L. Betty; Sinéad Murphy; Matthew R. Perrott; Adam N. H. Smith; Karen A. Stockin (Marine Biology, 2023)
Reproductive parameters were assessed in 64 male common dolphins ( Delphinus delphis ) examined post-mortem from strandings and bycatch in New Zealand between 1999 and 2020. The stages of male sexual maturation were assessed using morphological measurements and histological examination of testicular tissue. Age was determined via growth layer groups (GLGs) in teeth. The average age (ASM) and length (LSM) at attainment of sexual maturity were estimated to be 8.8 years and 198.3 cm, respectively. Individual variation in ASM (7.5–10 years) and LSM (190–220 cm) was observed in New Zealand common dolphins. However, on average, sexual maturity was attained at a similar length but at a marginally younger age (< 1 year) in New Zealand compared to populations in the Northern Hemisphere. All testicular variables proved better predictors of sexual maturity compared to demographic variables (age and total body length), with combined testes weight the best outright predictor of sexual maturity. Reproductive seasonality was observed in male common dolphins, with a significant increase in combined testes weight in austral summer. This aligns with most other studied populations, where seasonality in reproduction is typically observed. Given the known anthropogenic impacts on New Zealand common dolphins, we recommend that these findings be used as a baseline from which to monitor population-level changes as part of conservation management efforts.